1989
DOI: 10.1084/jem.169.1.269
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two distinct classes of streptococcal M protein and their relationship to rheumatic fever.

Abstract: Group A streptococci are human pathogens that infect primarily at the skin or nasopharyngeal mucosa . A major virulence factor present on the streptococcal surface is M protein, a molecule of which there exists more than 80 distinct serological types. M protein provides the streptococcus with the ability to resist phagocytosis by polymorphonuclear leukocytes, and only antibodies directed to type-specific determinants permit opsonophagocytosis in whole blood (1, 2). Structural studies reveal that M protein is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
134
0
7

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 28 publications
(54 reference statements)
7
134
0
7
Order By: Relevance
“…The demonstration that those strains that primarily cause pharyngitis and RF (class 1) have a different M-protein molecular structure from those strains that primarily cause skin infections and glomerulonephritis (class 2) supports the concept of rheumatogenic strains. 24 Our recent experience offers additional support that a limited number of M types are rheumatogenic and often are mucoid. Although M-18 was dominant, it was not the exclusive M type that was mucoid in the community.…”
Section: Discussionmentioning
confidence: 85%
“…The demonstration that those strains that primarily cause pharyngitis and RF (class 1) have a different M-protein molecular structure from those strains that primarily cause skin infections and glomerulonephritis (class 2) supports the concept of rheumatogenic strains. 24 Our recent experience offers additional support that a limited number of M types are rheumatogenic and often are mucoid. Although M-18 was dominant, it was not the exclusive M type that was mucoid in the community.…”
Section: Discussionmentioning
confidence: 85%
“…Preliminary evidence suggests that this putative lineage may represent the OF-positive serotypes. The conserved repeated regions of these two categories of M proteins are clearly different as determined by antibody-binding studies (4). In addition, DNA probes from various conserved regions within and surrounding OF-negative M protein genes bind much more strongly to chromosomal DNAs from other OF-negative serotypes than they do to DNAs from OFpositive serotypes (E. Haanes-Fritz, Ph.D. thesis, University of Minnesota, Minneapolis, 1989; E. Haanes, D. Heath, and P. P. Cleary, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the OF-positive strains are predominantly isolated from skin infections, as opposed to throat infections (37). Furthermore, Bessen et al recently demonstrated that antibodies directed against defined epitopes in the conserved domain of M6 bound to surface epitopes of OF-negative but not OF-positive strains (4). Detailed studies of M proteins from OF-positive strains have been hampered, however, by the fact that these M proteins tend to be less immunogenic than their OF-negative counterparts (53).…”
mentioning
confidence: 99%
“…The tendency to induce acute rheumatic fever is possibly the best-studied example. [9][10][11] Other determinants of virulence are encoded by a variety of chromosomal genes, many of which are associated with highly mobile phage elements. For these, the genetic links to virulence are far less clear and likely polygenic.…”
Section: Introductionmentioning
confidence: 99%